2013
DOI: 10.1136/jmedgenet-2012-101351
|View full text |Cite
|
Sign up to set email alerts
|

Breakpoint mapping by next generation sequencing reveals causative gene disruption in patients carrying apparently balanced chromosome rearrangements with intellectual deficiency and/or congenital malformations

Abstract: NGS is a powerful tool allowing rapid breakpoint cloning of ABCR at the molecular level. We showed that in three out of four patients, gene disruption could account for the phenotype, allowing adapted genetic counselling and stopping unnecessary investigations. We propose that patients carrying ABCR with an abnormal phenotype should be explored systematically by NGS once a genomic imbalance has been excluded by array CGH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
84
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 40 publications
0
84
0
6
Order By: Relevance
“…S7). In humans, numerous abnormal phenotypes, including intellectual disability and congenital anomalies, are caused by gene disruptions resulting from balanced rearrangements (Fruhmesser et al 2013;Schluth-Bolard et al 2013;Moyses-Oliveira et al 2015;Schneider et al 2015). This would occur in 6% of de novo reciprocal translocations and 9% of de novo inversions, but these events are detrimental and therefore remain rare in the population.…”
Section: Discussionmentioning
confidence: 99%
“…S7). In humans, numerous abnormal phenotypes, including intellectual disability and congenital anomalies, are caused by gene disruptions resulting from balanced rearrangements (Fruhmesser et al 2013;Schluth-Bolard et al 2013;Moyses-Oliveira et al 2015;Schneider et al 2015). This would occur in 6% of de novo reciprocal translocations and 9% of de novo inversions, but these events are detrimental and therefore remain rare in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Translocations can exert phenotypic effects either because of copy number changes in dosage-sensitive genes within the chromosome regions involved in the translocation or because of the disruption of genes at one or more of the breakpoints [Schluth-Bolard et al, 2013]. In the present cases, we hypothesized that it was less likely that gene disruption at the breakpoint had a significant contribution compared to the relative dosage effects caused by inheritance of a derivative chromosome.…”
Section: Discussionmentioning
confidence: 73%
“…Previous work has shown that paired-end mapping or mate pair sequencing has unprecedented resolution for the detection of SV breakpoints of balanced genomic rearrangements in patients with ID/MCA and may thus be a valuable tool for diagnostic implementation. [16][17][18][19][20][21][22][23] Here we made a systematic comparison between mate pair sequencing versus array CGH and karyotyping. As a first important conclusion from this work, we demonstrate that all types of pathogenic SVs previously found with array CGH or karyotyping could also be found using a combined strength of the cluster and DOC signatures of mate pair sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Korbel et al 15 were the first to use NGS to map structural variations in the human genome, and several other groups have used this technique to finemap the breakpoints of specific structural aberrations (mostly apparently balanced chromosomal aberrations) in patients with ID/MCA. [16][17][18][19][20][21][22][23] Therefore, the technique has proven its usability in characterizing individual SVs. Here we describe the first systematic comparison between mate pair sequencing, genomic microarrays and karyotyping in a large cohort of ID/MCA patients referred to our diagnostic departments.…”
Section: Introductionmentioning
confidence: 99%